A new species of Comatulidae (Echinodermata: Crinoidea) from the southwestern Atlantic coast - Souza, Tulio H. De; Martins, Luciana; Fukuda, Marcelo; Souto, Camilla (Zootaxa, 2025)
In this paper we describe a new species of Comatulidae based on specimens collected in Campos Basin, off the Southern Brazilian coast at depths ranging from 64 to 202 m. Comactinia auxiliadorae sp. nov. differs from other species in the genus by having pinnules P2, P3, Pb and Pc reduced or absent; proximal pinnulars of the oral pinnules triangular or shield-shaped, with spines on the aboral edge, and without carinae; oral pinnules bearing 3–7 teeth, confluent with exterior edge of the arm. In addition to the species description and photographs, an identification key to the genus Comactinia and a brief discussion about the comb teeth morphology are provided. The new species represents the first Crinoidea from the Brazilian coast described in the last 100 years and the first crinoid species from Brazil described by Brazilian researchers.